Investigate The Safety Profile of Metronidazole, Exploring Potential Adverse Effects And Toxicity - Sarvesh , K.; Navneet , S.; Prasant , A.; Vivek , S.; Payal , V.; Sanjeev , K.; Peeush, S. (Journal of Neonatal Surgery, 2025)
This analysis takes an in-depth look at the safety profile of metronidazole, a popular antibiotic that works well against anaerobic bacteria and parasites. The development of medicine over time, starting with the discovery of azomycin, demonstrated its ability to treat diseases, particularly trichomoniasis and giardiasis. The way metronidazole works is that it forms a cytotoxic intermediate intracellularly that damages the bacterial DNA, thereby clearing the anaerobic infection. The pharmacology of metronidazole encompasses diverse formulations, rapid absorption, and extensive tissue penetration. While generally well-tolerated, metronidazole presents considerations for dosage, duration, and patient-specific factors to minimize toxicity risks. Despite its efficacy, rare instances of resistance and adverse effects, such as neurotoxicity and hepatotoxicity, warrant cautious use. This review delves into metronidazole-induced complications, including neurotoxicity, encephalopathy, and pancreatitis. Risk mitigation and monitoring strategies are outlined, emphasizing patient assessments, dosage adjustments, and organ function monitoring. Specific considerations for pregnant individuals and potential cytogenetic effects are also discussed. In conclusion, while metronidazole remains a cornerstone in antimicrobial therapy, its judicious use requires an understanding of therapeutic benefits and associated risks. The review provides insights into metronidazole's intricate pharmacology, toxicity factors, and strategies for optimizing patient safety during clinical use. Ongoing research and vigilant clinical practices are crucial for ensuring the sustained efficacy of metronidazole across diverse medical contexts